Chromosome Number and Secondary Chromosome Associations in Wild Populations of Geranium Pratense L. from the Cold Deserts of Lahaul-Spiti (India) - Kumar, P.; Singhal, V.K. (Цитология и генетика, 2013)
In this work we studied the meiotic chromosome number and details of secondary chromosomal associations recorded for the first time in Geranium pratense L. from the alpine environments in the cold deserts of LahaulSpiti (India). All the presently studied individuals of the species existed at 4x level (x = 14). The present chromosome count of n = 28 in the species adds a new cytotype to the already existing diploid chromosome count of 2n = 28 from the Eastern Himalayas and outside of India. Out of the six accessions scored presently four showed normal meiotic course. However, two accessions investigated from Mud, 3800 m and Koksar, 3140 m depicted abnormal meiotic course due to the presence of multivalents and univalents, and secondary associations of bivalents/chromosomes. The secondary chromosomal associations in the species existed among bivalents/chromosomes were noticed in the PMCs at prophaseI (diakinesis) and persisted till the separation of sister chromatids at MII. The variation in the number of bivalents/chromosomes involved in the secondary associations at MI (2–8) and AI/MII (2–12) has also been recorded. The occurrence of such secondary associations of bivalents/ chromosomes in G. pratense which existed at 4x level indicated the secondary polyploid nature of the species.